Examining the Study Behavior of Isfahan University Graduate Students within a Digital Environment based on Demographic Factors - Fatima Naderi; ahmad shabani; Muhammad Reza Abedi (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2010)
Objective: To investigate the study behavior displayed by Isfahan University graduate students when immersed in a digital environment. Methodology: A survey using self-designed questionnaire was carried out. Content validity was audited by a number of LIS Faculty members and their suggestions were duly employed. The sample was 286 students randomly selected from 3892 graduate students. Findings: The Engineering and Technology Faculty had the highest rate of studying of electronic resources, while the Science Faculty had the highest number of hardprints from the said resources. Students are more inclined towards a non-linear browsing and rarely engage in deep and critical studies. Phd candidates mostly use browsing while graduate students take a hardprint of electronic documents. No significant difference was observed between males and female [students].